A High Sensitive TNT Sensor Based on Electrochemically Reduced Graphene Oxide‐Poly(amidoamine) Modified Electrode. Issue 6 (18th March 2015) - Shamsipur, Mojtaba; Tabrizi, Mahmoud Amouzadeh; Mahkam, Mehrdad; Aboudi, Javad
Abstract In this paper, the electrochemically reduced graphene oxide‐poly(amidoamine) hybrid (ErGO‐PAMAM) have been used for fabrication of TNT electrochemical sensor. The prepared modified electrode is characterized with X‐ray photoelectron spectroscopy (XPS), fourier transform infrared spectroscopy (FT‐IR), electrochemical impedance spectroscopy (EIS), energy‐dispersive X‐ray (EDX) spectroscopy, scanning electron microscopy (SEM) and atomic force microscope (AFM). Based on obtained results, it is can be seen that the ErGO‐PAMAM/GCE has high response to TNT than the other graphene based modified electrodes. The resulting electrochemical sensor exhibited good response to TNT with linear range from 0.05 to 1.2 ppm with a low detection limit of 0.0015 ppm.